Hybrid Business Model for Airlines and the Sources of its Value - Monika PASIK (Communications of International Proceedings, 2021)
In connection with the dynamically changing market conditions the air carriers are looking for tools to support their operations. Moreover the unstable situation resulting from the pandemic increased the need for additional support in the management of company.  In such circumstances, a business model may be useful. This paper compares and characterizes 3 business models for airlines: the traditional model, the low cost model, and the hybrid model on the example of the LOT Polish Airlines, Ryanair, and airBaltic. The main purpose of the study was to identify the value sources in the hybrid model. Using the desk research technique, benchmarking the models, and using a survey form, 9 factors that help create values in hybrid airlines could be specified. The questionnaire survey made it also possible to point out the preferences of prospective customers concerning choice of an airline.
Keywords: Business Models; Value Sources; Air Carriers; Hybrid Model